2018
DOI: 10.3390/molecules23030586
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Condensed Tannins from Purple Prairie Clover (Dalea purpurea Vent.) Conserved as either Freeze-Dried Forage, Sun-Cured Hay or Silage

Abstract: Conservation methods have been shown to affect forage nutrient composition and value, but little information is available about the effect of forage conservation on plant condensed tannins (CT). The objective of this study was to assess the effects of conservation method on the concentration, chemical composition and biological activity of CT. Whole-plant purple prairie clover (PPC, Dalea purpurea Vent.) was harvested at full flower and conserved as freeze-dried forage (FD), hay (HAY) or silage (SIL). Concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 69 publications
5
14
0
Order By: Relevance
“…It is worth highlighting that these experiments showed that upon ensiling FV without inoculation, the ratios of the characteristic peaks of polyphenols are comparable to that of the fresh (i.e., pre-ensiled) seaweed. This suggests that the structures of phlorotannins remain intact during the ensiling process; a similar finding was observed in tannin-containing terrestrial silages [51]. Hence, we would expect seaweed silage to have a similar bioactivity compared to pre-ensiled seaweeds, but further studies would be needed to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 56%
“…It is worth highlighting that these experiments showed that upon ensiling FV without inoculation, the ratios of the characteristic peaks of polyphenols are comparable to that of the fresh (i.e., pre-ensiled) seaweed. This suggests that the structures of phlorotannins remain intact during the ensiling process; a similar finding was observed in tannin-containing terrestrial silages [51]. Hence, we would expect seaweed silage to have a similar bioactivity compared to pre-ensiled seaweeds, but further studies would be needed to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 56%
“…Compared to fresh forage, concentrations of extractable CT have been shown to be lower in hay 11,12 and silage, 3,4,13 but the concentration of total CT was not altered by either of these conservation methods. Peng et al 4 . found that ensiling had a more profound effect than drying on the chemical composition and protein‐precipitating capacity of CT.…”
Section: Introductionmentioning
confidence: 94%
“…Condensed tannins (CT) are a group of naturally occurring plant secondary compounds that possess antioxidant, antimicrobial and antiparasitic activities and are known for their ability to precipitate proteins 1–4 . Therefore, forages containing CT have been extensively evaluated under grazing conditions, although fewer studies have been conducted in intensive ruminant production systems 5–7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigallocatechin, catechin, epicatechin and gallocatechin were identified in Purple Prairie Clover (Dalea purpurea Vent.) (Peng et al, 2018).…”
Section: Concenmentioning
confidence: 99%